Injury surveillance during the 2010 IRB Women's Rugby World Cup. Issue 15 (22nd September 2011) - Taylor, Aileen E; Fuller, Colin W; Molloy, Michael G
Abstract : Objective: To assess and evaluate injuries sustained during the 2010 Women's Rugby World Cup. Design: Prospective, cohort. Participants: 285 women rugby players. Results: Incidence of match injury was 35.5/1000 player-hours; mean severity was 55.0 days and median severity 9 days. Only one training injury was reported. Knee-ligament injuries were the most common (15%) and resulted in most days lost (43%). The tackle was the cause of most injuries. Conclusions: The risk of injury in international rugby is significantly lower for women than for men. Further research is required to assess knee-ligament injuries in women's rugby.